2013 Proceedings IEEE INFOCOM 2013
DOI: 10.1109/infcom.2013.6567074
|View full text |Cite
|
Sign up to set email alerts
|

PSR: Practical synchronous rendezvous in low-duty-cycle wireless networks

Abstract: Abstract-Low-duty-cycle radio operations have been proposed for wireless networks facing severe energy constraints. Despite energy savings, duty-cycling the radio creates transient-available wireless links, making communication rendezvous a challenging task under the practical issue of clock drift. To overcome limitations of prior work, this paper presents PSR, a practical design for synchronous rendezvous in low-duty-cycle wireless networks. The key idea behind PSR is to extract timing information naturally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…It can be observed that the transmission periods are randomly distributed within the interval [30.28s, 30.35s]. Moreover, the distribution can be approximated by a Gaussian distribution [7], which is also validated by our experimental results ( Fig.3(b)). 10 20 Such considerable variation of transmission period is mainly caused by two reasons.…”
Section: B Stochastic Transmission Patternsupporting
confidence: 82%
See 2 more Smart Citations
“…It can be observed that the transmission periods are randomly distributed within the interval [30.28s, 30.35s]. Moreover, the distribution can be approximated by a Gaussian distribution [7], which is also validated by our experimental results ( Fig.3(b)). 10 20 Such considerable variation of transmission period is mainly caused by two reasons.…”
Section: B Stochastic Transmission Patternsupporting
confidence: 82%
“…In these works, the transmission period, i.e., the duration between each two consecutive transmission instances of one node, is considered as a constant. However, owing to the clock drift (illustrated in Transmission Stage in Fig.2) as well as the uncertainties during the sensing, computation and communication processes [7], the practical transmission periods turn out to be dynamic and random values which possibly deteriorate the effects of many existing attacking strategies. For example, setting the frame length as 30s, we conducted experiments over the MicaZ node which was equipped with sensor and set to transmit packets about the temporal temperature under the transmission rate of 250kbps.…”
Section: B Stochastic Transmission Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Duty cycling is a critical technique to enable long-term operations [11], [28], [36] for battery-powered devices, where radios turned off for the majority of the time. FreeBee messages are continuously transferred over the air without overwhelming the channel, thereby safely reaching mobile and/or duty cycled receivers without the need for complex rendezvous techniques [17], [22]. Moreover, interval multiplexing enables (iv) concurrent many-to-many communication to further enhance the practicality under today's crowded wireless devices.…”
Section: E Summary Of Unique Design Benefitsmentioning
confidence: 99%
“…For any message, the time that passes from the start of broadcast attempt until the recipient node receives it is referred as transmission delay. Based on central limit theory and empirical observations [10], we model the transmission delays as a Gaussian distributed random variable, denoted by T ∼ N (0, σ 2 d ). The logical clock l u () of node u can be modeled as…”
Section: Arxiv:151202977v1 [Csdc] 9 Dec 2015mentioning
confidence: 99%